Wikinomics how mass collaboration changes everything - Tapscott, Don 1947-; Williams, Anthony D. (Portfolio, 2006)
In just the last few years, in one of the most profound changes of our time, traditional collaboration--in a meeting room, a conferencec all, even a convention center--has been superseded by collaborations on an astronomical scale. Today, encyclopedias, jetliners, operating systems, mutual funds, and many other items are being created by teams numbering in the thousands or even millions. Flickr, Second Life, YouTube, and other thriving online communities transcend social networking to pioneer a new form of collaborative production. While some leaders fear the heaving growth of these massive online communities, Wikinomics shows this fear is folly. Smart firms can harness collective capability and genius to spur innovation, growth, and success. Mature companies can cultivate nimble, trust-based relationships with external collaborators to form vibrant business ecosystems. Wikinomics challenges our most deeply-rooted assumptions about business and aims to be a road map for doing business in the 21st century.--From publisher description.
Includes index
Keywords: Créativité dans les affaires; Economische aspecten; Réseaux d'affaires; Samenwerking; Vernieuwing; Virtuele gemeenschappen; Wirtschaft; Business networks; Creative ability in business; Social Media; Unternehmen; Netzwerkmanagement; Soziale Software; Internet; Vernetzung; Massenkommunikation; Wiki; Innovationsmanagement